Teachers’ Techniques in Improving Students Pronouncing Words Loudly at the First Year of MAN Batam. - Taqiyuddin Taqiyuddin; Cynda Gemala Dewi (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
This research has three research questions. The first research question is “What techniques the teacher use in improving students pronouncing words loudly at the first year of MAN Batam?” the second is “Which technique frequently used by the teacher in improving students pronouncing words loudly at the first year of MAN Batam ?” and third is what might made the teacher prefer to the technique? Moreover, the subject of the study are two English teachers. Meanwhile, the object of the study is the teachers’ techniques in improving students pronouncing words loudly at the first year of MAN Batam . In this research, the researcher took two teachers as the respondent. The techniques of collecting data are observation and interview. Observation is used to know the teacher technique in teaching pronounciation. And interview is used to know the effectiveness of technique in teaching pronounciation. The researcher uses observations as main data collection and the interview is as to support the data needed. In addition to the data analysis, the researcher uses descriptive quantitative which applies statistical data. To know the percentage, the researcher used formula as follow: P As for the result of this research, the researcher takes some conclusions. They are: English teacher uses drilling technique how to pronounce the word, English teacher uses repetition technique to practice and improve students pronouncing, English teacher uses backward building up technique to improve students pronouncing, and End the repetition technique is the most frequently used by the teacher. Based on the analysis of data, the researcher concludes that The Teachers’ Techniques in Improving Students Pronouncing Words Loudly at the first year of MAN Batam is categorized into “less”.